A contrastive analysis of grammatical and semantic features of words and idioms related to “hearing” in english and vietnamese - Lê Xuân Thanh Giang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study under the title “ A contrastive analysis of grammatical and semantic features of words and idioms related to “hearing” in English and Vietnamese” is a great attempt to provide a comprehensivve account of grammatical and semantic features of the linguistic iterms including words and idioms. These items are grammatically and semantically analyzed to explore the similarities and differences in the use of these verbs and idioms in the two language systems. Thus, the study may enable the learners, teachers and users to have happy choice of word for different contexts so that they can reach their communicative aims. Accordingly, some suggestions to the language teaching and learning have been offered in the hope that Vietnamese learners of English can get great benefit from the study